Real-world experience: a retrospective pediatric chart review to determine why patients and caregivers discontinue oral immunotherapy - Amy A. Plessis; Scott B. Cameron; Rosemary Invik; Mariam Hanna; Douglas P. Mack; Victoria E. Cook (Allergy, Asthma & Clinical Immunology)
Abstract Background Oral immunotherapy (OIT) is an increasingly utilized management strategy for IgE-mediated food allergy. Despite promising efficacy and effectiveness, there is still a lack of data surrounding the reasons for discontinuation of OIT. The primary reason stated in the literature for discontinuation is adverse gastrointestinal effects. Social factors contributing to OIT discontinuation have not been well reported. We hypothesize that social considerations are significant contributors to treatment discontinuation. Methods We completed a retrospective chart review of 50 patients treated in community pediatric allergy practices who discontinued OIT out of 507 patients who were started on OIT between October 1, 2017-October 27, 2022. Reasons for discontinuation were identified and classified into five main categories: unsafe care decisions, anxiety, adverse effects of OIT, uncontrolled comorbidity and social factors. Categories were not exclusive. Results 507 patients were started on OIT, with data available for 50 patients who discontinued OIT, aged 10 months to 18 years and 2 months. The overall discontinuation rate was 9.8%, of which 40 patients (80%) discontinued during buildup, 9 patients (18%) discontinued during maintenance and one patient on two food OIT discontinued one food during buildup and one during maintenance (2%). Thirty-four patients (68%) had multiple reasons for discontinuing OIT. Social factors were the most common reason for discontinuation and were identified in 32 patients (64%). Twenty-four patients (48%) discontinued OIT due to adverse effects. Gastrointestinal symptoms were the most prevalent, while anaphylaxis contributed to discontinuation in 15 patients (30%). Anxiety led to discontinuation in 17 patients (34%). Conclusions Our data highlights the importance of social factors and anxiety in the success of OIT completion. Our results support the need to consider not only the patient’s medical history, but also their social history and support networks when selecting patients who are good candidates for OIT to optimize the successful completion of OIT.